Convalescent Plasma Therapy in COVID-19 Patients with Acute Respiratory Distress Syndrome (ARDS) - Dewi Arum Sawitri; Arie Zainul Fatoni (Jurnal Respirologi Indonesia, 2023)
COVID-19 is caused by SARS-CoV-1, an RNA virus of the betacoronavirus genus, making it the seventh coronavirus infecting humans. Because particular therapies are still in the research stage, no confirmed treatment for this illness has been agreed upon by the World Health Organization (WHO) or other clinical institutes. The reason is that there are many different potential remedies. Antiviral treatments like favipiravir, oseltamivir, and remdesivir have been investigated and tested. On the other hand, the outcomes of the replies of patients who were given these medications are still quite inconsistent. Furthermore, the COVID-19 mortality rate has remained at a level of less than 5.21 percent of cases that have been documented. Patients suffering from COVID-19 may be treated with convalescent plasma, a therapeutic option that utilizes a mix of neutralizing antibodies and other immunological components. Activation of body-dependent cellular cytotoxicity (ADCC) and phagocytic activity against COVID-19 will occur due to this immunological component. This medication also has the potential to reduce the systemic inflammatory response brought on by COVID-19. Clinical improvement was different after 28 days when convalescent plasma was used as a treatment for patients with severe COVID-19 symptoms and emergency conditions compared to patients treated with conventional therapy alone. However, it is not very significant.